Nonlinear and Linear System Identification Step Reflux Flow Rate for Distillation Column - Mohd Shaib, Siti Nur Fatihah (Universiti Teknologi PETRONAS, 2016)
Distillation column is one of the important process operation units in the chemical industry. As known by all engineers, distillation column has unpredictable and complex in nature. This is because of the high purities of the product and making them difficult to handle. Therefore, system identification is introduced in this project to identify and estimate mathematical models of dynamic models of dynamic system of distillation column for measured data. The identification was done to accomplish the stability of the distillation column through simulation by obtaining linear and nonlinear process models using System Identification Toolbox. There have 3 objectives should be meet in the end of this project. First is to obtain the various parameter stability of distillation column through simulation. Next, to acquire the linear and non-linear process models using System Identification Toolbox. Lastly to evaluate the data attained and plot the required charts.